O conceito de aparência em Hannah Arendt: do desmantelamento da metafísica à dignidade da política - Dias, Lucas Barreto (2014)
Hannah Arendt’s concept of appearance has a central importance in the entirety of her work. This is the hypothesis of our research and, based on it, the aim of this dissertation is to comprehend how this question arises in many moments of Arendt’s thought. From her last book – The life of the mind –, the definitions that refer to the value of the surface in its several aspects receive some notability. With intention that is possible to find the references on the concept of appearance in its very moments, this work tries to achieve a double explanation of this concept showing their basic dimensions: the philosophical and the political. Arendt’s dismantling of metaphysics shows itself important to raise the dignity of appearance; thus, some concepts like truth, reason, thought, mind, intellect and cognition become central pieces. In constant debate with philosophical tradition, this dissertation aims to indicate how appearance receive another mean by Hannah Arendt in such way that terms as reality/realness, world, thought and judgment shows itself indispensable for recover the dignity of world’s phenomenal nature. Although, the hypothesis would be incomplete if it doesn’t demonstrate this dignity as indispensably related to man’s and politics’ dignities. Then, it makes an appreciation about how Arendt’s political theory – The human condition is the major theoretical bases here – is permeate in all its levels by the concept of appearance. The concepts developed to this purpose are: public sphere, action, speech, power and freedom. Lastly, the totalitarian event was elected as a crucial moment to think the appearance’s loss for politics. From this, it resulted what we called world of semblances, that is, the destruction performed by totalitarianism of the common world and the creation of a fictional world. This analysis had in its development the concept of semblance treated in the first part of the dissertation and the read, made from this, of the third part of The origins of totalitarianism, whence rises to discussion the propaganda, the organization, the secret police, the extermination camps, the ideology and the terror. The research, thus, brings an interpretation on the concept of appearance to show it as central and indispensable for the comprehension of the themes related to the mind activities as such as to those things associated to the world and the human affairs, revealing, then, that the dignity of appearance brings to the dignity of politics as well as the loss of the appearance reverberate in the loss of the dignity of politics.